Modal analysis of two different types of fixed implant-supported prostheses embedded in edentulous maxillae. Issue 3 (July 2019) - Suzuki, Akihiro; Hoshiai, Taiji; Nakata, Hidemi; Otomaru, Takafumi; Oki, Meiko; Taniguchi, Hisashi; Kasugai, Shohei; Kuroda, Shinji
Abstract: Purpose: Modal analysis has been used to monitor and quantify the vibration of each component of a prosthesis at its natural frequency. An understanding of the vibrational characteristics of a prosthesis can guide selection of the appropriate prosthesis configuration to prevent excessive stress. In this study, modal analysis of fixed implant-supported prostheses with 4 or 6 abutments in edentulous maxillae was performed. Methods: Sixteen patients underwent maxillary dental implant treatment and received screw-fixed implant-supported prostheses (9 patients received 4-abutment prostheses and 7 patients received 6-abutment prostheses) in edentulous maxillae. An impact hammer was used for excitation of the prostheses, and vibration was detected on every crown of the prostheses. The modal parameters were determined in each subject. Furthermore, the modal shapes were compared at each natural frequency. Results: The median natural frequencies of subjects with 4- and 6-abutment prostheses were 697 and 781 Hz, respectively. The mean damping ratios did not differ significantly between 4- (8.2 ± 1.7%) and 6-abutment (6.6 ± 1.7%) prostheses ( p  = 0.125). The mean maximum displacements of fixed prostheses were significantly lower for 6-abutment (10.3 ± 3.3 μm) than for 4- (20.3 ± 9.1 μm) prostheses ( p  = 0.004). The median number of vectors in antiphase was significantly lower for 6- (4) than for 4-abutment prostheses (14) ( p  = 0.001). Conclusions: The current study demonstrated less adverse vibration in the 6-abutment prostheses than in the 4-abutment prostheses, suggesting that modal analysis can contribute to novel future developments in the designs of dental implant prostheses.